2020
DOI: 10.1016/j.heliyon.2020.e03284
|View full text |Cite
|
Sign up to set email alerts
|

Effect of storage time on the quality of smoked Oreochromis niloticus

Abstract: Effect of storage time on the quality of smoked Oreochromis nilotius was studied. One hundred fish samples of O. niloticus (average weight 210 AE 15g) was used. Analysis carried out include: proximate, mineral composition (Ca, Na, Fe and Mg), biochemical, amino acid and sensory evaluation. Data obtained was subjected to Analysis of Variance (ANOVA) while the sensory data was subjected to nonparametric test (Kruskal Wallis test). Proximate quality, mineral, amino acid, biochemical and sensory quality of frozen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 8 publications
1
8
0
1
Order By: Relevance
“…Therefore protein in hot smoked llets decreased after 20 and 90 days of storages. This last nding is mainly due to the autolytic enzymes activities causing spoilage [13]. This decrease in protein, associated with the storage time, could be also explained by the microbial spoilage [14].…”
Section: Totalmentioning
confidence: 96%
“…Therefore protein in hot smoked llets decreased after 20 and 90 days of storages. This last nding is mainly due to the autolytic enzymes activities causing spoilage [13]. This decrease in protein, associated with the storage time, could be also explained by the microbial spoilage [14].…”
Section: Totalmentioning
confidence: 96%
“…Ayeloja, Jimoh, Adetayo, et al. (2020) reported that dieticians recommend the consumption of fish to prevent cardiovascular diseases and some other malnutrition‐related ailments due to the presence of essential amino acids as well as some nitrogenous compounds, water, lipids, carbohydrates, minerals, and vitamins in fish. Ravichandran et al.…”
Section: Introductionmentioning
confidence: 99%
“…(2011) also reported that fish is a good source of antimicrobial peptides, which defend the body against dreadful human pathogens. However, fish is a highly perishable food due to its high water activity, protein content, and activities of autolytic enzymes, which cause spoilage (Ayeloja, Jimoh, Adetayo, et al., 2020). Eyo (2001) stated that most of the fish produced in the remote coastal centers and hinter land of many tropical countries perish before they reach consumers due to poor handling and preservation techniques adopted by fishermen as well as lack of fish storage facilities.…”
Section: Introductionmentioning
confidence: 99%
“…Ayeloja (2019) stated that many preservative methods are employed in extending fish shelf life including smoking, sun drying, canning, solar drying among others. However, smoking is the most adopted method in many developing countries (Ayeloja et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%